ASSETS COMPOSITION AND MARKET VALUE OF INDUSTRIAL GOODS FIRMS IN NIGERIA (Journal of Global Accounting, 2024)
This study determined the effect of assets composition on financial performance of industrial goods in Nigeria. Specific objectives are to: determine the effect of Non-current assets on financial performance of listed industrial goods firms in Nigeria and ascertain the extent current assets turnover on financial performance of listed industrial goods firms in Nigeria. This study was adopted Ex Post Fact research design. The population of the study consists of twelve (12) listed industrial goods firms in Nigeria. Since the population size is not large, the researcher used a consensus sampling to adopt all the population for the study.  Data were extracted from the annual reports and accounts of industrial goods firms in Nigeria 2013 to 2022. Data were analyzed with descriptive statistics, and the hypotheses were tested with Pearson correlation, and multiple regression analysis. The result revealed that P-value of the test was 0.000 less than 0.05 (5%), this study upholds that non-current assets has significantly affect financial performance of listed industrial goods firms in Nigeria. also, the second result revealed that P-value of the test was 0.000 less than 0.05 (5%), this study upholds that current assets turnover has significantly affect financial performance of listed industrial goods firms in Nigeria.  the study recommended that the management of industrial goods firms should carefully consider the levels of their non-current assets investments, as they may not make any meaningful contribution to financial performance.
Keywords: Assets composition; Current assets turnover; Financial performance; Non-current assets.